2019
DOI: 10.1038/s41467-019-13211-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to defense metabolites and evading fruit bitterness in genus Solanum evolved through 2-oxoglutarate-dependent dioxygenases

Abstract: The genus Solanum comprises three food crops (potato, tomato, and eggplant), which are consumed on daily basis worldwide and also producers of notorious anti-nutritional steroidal glycoalkaloids (SGAs). Hydroxylated SGAs (i.e. leptinines) serve as precursors for leptines that act as defenses against Colorado Potato Beetle (Leptinotarsa decemlineata Say), an important pest of potato worldwide. However, SGA hydroxylating enzymes remain unknown. Here, we discover that 2-OXOGLUTARATE-DEPENDENT-DIOXYGENASE (2-ODD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 45 publications
3
93
0
Order By: Relevance
“…The content of downstream SGAs decreases gradually after the Br period along with the expression of the downstream biosynthesis-related gene GAME31 . These results are consistent with those of a previous study [ 40 ].
Fig.
…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The content of downstream SGAs decreases gradually after the Br period along with the expression of the downstream biosynthesis-related gene GAME31 . These results are consistent with those of a previous study [ 40 ].
Fig.
…”
Section: Resultssupporting
confidence: 94%
“…7 a). In contrast, GAME31 was mainly expressed at the tomato fruit ripening stage and catalyzes the first important step in the chemical shift after maturation within nonbitter SGA by a hydroxylation reaction [ 39 , 40 ]. Interestingly, we found that the different expression patterns between GAME11 and GAME31 resulted in the appropriate function at the right time.…”
Section: Resultsmentioning
confidence: 99%
“…The high α‐tomatine levels in immature fruit decrease during ripening by the conversion to esculeoside A (Fig. 1; Mintz‐Oron et al ., 2008; Iijima et al ., 2009; Cárdenas et al ., 2019; Nakayasu et al ., 2020). The antimicrobial activity of α‐tomatine was first demonstrated on the fungal pathogen Fusarium oxysporum f. sp.…”
Section: α‐Tomatine: the Major Tomato Saponin With Antibiotic Activitymentioning
confidence: 99%
“…Tomato and eggplant, on the other hands, contain only spirosolane glycoalkaloids 3 , 13 . In tomato, α-tomatine 5 and dehydrotomatine 6 are predominant in green tissues, while the non-bitter SGA esculeoside A is the major component in the red mature fruits 14 , 15 . α-Solasonine and α-solamargine are the two major spirosolane glycoalkaloids produced in eggplant 16 .…”
Section: Introductionmentioning
confidence: 99%